2020
DOI: 10.21037/qims.2020.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial extracellular volume on body computed tomography in breast cancer patients treated with anthracyclines

Abstract: Background: Cancer treatment with anthracyclines may lead to an increased incidence of cardiac disease due to cardiotoxicity, as they may cause irreversible myocardial fibrosis. So far, the proposed methods for screening patients for cardiotoxicity have led to only limited success, while the analysis of myocardial extracellular volume (mECV) at cardiac magnetic resonance (CMR) has shown promising results, albeit requiring a dedicated exam. Recent studies have found strong correlations between mECV values obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
5
17
0
Order By: Relevance
“…Although this might be ideal, most oncologic follow-up CT protocols do not include delayed phase scans after the portal venous phase, in order to spare radiation exposure to the patient. A previous work [25] showed good correlations between myocardial ECV values obtained at 1, 3, and 7 min after contrast injection in breast cancer patients who underwent thoracic CT; hence, we can speculate that the portal venous phase we considered in the current work (approximately 80 s after contrast injection) allowed to measure values of relative enhancement readable as CT-derived ECV values. Secondly, most of our patients underwent combined chemoradiotherapy, making it impossible to discern the individual impact of either radiation or drug therapies.…”
Section: Discussionmentioning
confidence: 59%
“…Although this might be ideal, most oncologic follow-up CT protocols do not include delayed phase scans after the portal venous phase, in order to spare radiation exposure to the patient. A previous work [25] showed good correlations between myocardial ECV values obtained at 1, 3, and 7 min after contrast injection in breast cancer patients who underwent thoracic CT; hence, we can speculate that the portal venous phase we considered in the current work (approximately 80 s after contrast injection) allowed to measure values of relative enhancement readable as CT-derived ECV values. Secondly, most of our patients underwent combined chemoradiotherapy, making it impossible to discern the individual impact of either radiation or drug therapies.…”
Section: Discussionmentioning
confidence: 59%
“…The ECV was calculated by combining native and post-contrast T1, and hematocrit reflecting an expanded extracellular matrix (15). Previously, Monti et al demonstrated that contrast-enhanced computed tomography also has potential value for assessing ECV (24). In recent years, researchers have reported on the application of T1 mapping technology in non-rheumatic valvular diseases, such as aortic stenosis, and aortic and mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…While our population was already involved in a previous work assessing the role of myocardial extracellular volume as a biomarker of anthracycline cardiotoxicity [ 14 ], such analyses require the presence of both unenhanced and contrast-enhanced CT scans including the heart and might therefore prove less widely feasible than the sole assessment of EAT density on unenhanced scans, hence providing an edge to the use of EAT density in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we excluded all CT scans which presented artefacts that would hinder the segmentation of EAT, SAT, or VAT. Our patient population was already included in a study appraising the role of myocardial extracellular volume in anthracycline cardiotoxicity [ 14 ]. For each patient, we retrieved demographical, BC, staging, and treatment data.…”
Section: Methodsmentioning
confidence: 99%